EFFECTIVENESS OF BASIC HSSE TRAINING IN IMPROVING WORKERS’ KNOWLEDGE IN AN UPSTREAM OIL AND GAS COMPANY - Agustianto, Nicko; Novrikasari, Novrikasari; Windusari, Yuanita; Misnaniarti, Misnaniarti; Sitorus, Rico Januar; Syakurah, Rizma Adlia (UNG, 2026)
The oil and gas industry is a sector with a very high risk of occupational accidents due to its operational characteristics, which involve hazardous environments and unsafe worker behavior. Although Basic HSSE Training has become a mandatory standard in the oil and gas industry, evaluating its effectiveness remains urgent to ensure that the training is not merely a formality for regulatory compliance, but is truly aligned with the specific operational risks, work environment, and safety culture of Company. This study uniquely combines a pretest–posttest evaluation of Basic HSSE Training with an analysis of key organizational factors using multivariate statistical methods to identify dominant drivers of knowledge improvement among upstream oil and gas workers. This study aims to evaluate the effectiveness of Basic HSSE Training by measuring differences in workers' knowledge levels before (pre-test) and after (post-test) the training, as well as examining the influence of organizational factors management commitment, safety policies, regulations and procedures, HSSE communication, work environment, and worker involvement on knowledge improvement. A quantitative approach with a pretest–posttest design was employed, involving 303 workers at Company X in the upstream oil and gas sector in South Sumatra Province. Data were collected using Likert-scale questionnaires and multiple-choice tests. The Paired Samples t-test results indicate that Basic HSSE Training is effective in improving workers' knowledge, while Chi-Square and logistic regression analyzes show that organizational factors, particularly communication and work environment, play a dominant role in influencing the effectiveness of the training.